On the Theory of "Second Best" - Bohm, P. (Review of Economic Studies, 1967)
Journal Article On the Theory of "Second Best" Get access P. Bohm P. Bohm University of Stockholm Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 3, July 1967, Pages 301–314, https://doi.org/10.2307/2296678 Published: 01 July 1967